Two new species of the feather mite genus Trouessartia (Acari: Trouessartiidae) from Asia - Constantinescu, Ioana Cristina; Cobzaru, Ioana; Mukhim, D. Khlur B.; Adam, Costică (Zootaxa, 2016)
Two new feather mite species of the genus Trouessartia Canestrini are described from birds captured in Meghalaya (India): Trouessartia longidenticulata Constantinescu sp. n. from Pycnonotus cafer (Linnaeus) (Passeriformes, Pycnonotidae) and Trouessartia dicruri Constantinescu sp. n. from Dicrurus aeneus (Vieillot) (Passeriformes, Dicruridae). In the genus Trouessartia, males of T. longidenticulata show a unique character state in having the lamellae of the opisthosomal lobes with long and sharp denticles. Both sexes of T. dicruri differ from closely related T. delicatula Gaud, 1952 by smaller body size (T. dicruri males are 420–452 long, females 500–532 long, vs. c. 575 and 595, respectively in T. delicatula); males have the adanal apodemes without apophyses and the terminal lamellae in a shape of a parallelogram (vs. the adanal apodemes have a pair of apophyses and the terminal lamellae are semi-ovate); the opisthosomal lobes do not touch each other at the inner margins (vs. the opisthosomal lobes touch each other at the inner margins, at the level of setae h3); in females, setae h1 are lanceolate (vs. spiculiform).